Manual of the Warrior of Light - Paulo Coelho (Harper Collins, 2002)
A collection of insightful philosophical thoughts and stories, in which Paulo Coehlo offers inspiring answers to profound questions to delight spiritual seekers everywhere. It has proved to be a perfect gift-book in the few countries in which it has been published so far. This will be the first English translation. This book is a jewel for all of us who look for meaning in our daily lives as we struggle along the spiritual path. Within each of us is a Warrior of Light. Each of us capable of listening to the silence of the heart, of accepting failure without letting it get us down and of holding onto hope even in the face of weariness and depression. Values like love for all things, discipline, friendship and learning to listen to our own hearts are the arms with which this warrior confronts the battles we face in the name of personal growth and in the defence of the light. On every page there is an inspirational thought, which can be read as part of Paulo Coelho's whole philosophy or used form the basis of a daily meditation. The Manual of the Warrior of Light is a handbook that shows human beings how to live as spiritual beings in the material world.